meta- and para-Functionalized Thermally Crosslinkable OLED-Materials through Selective Transition-Metal-Catalyzed Cross-Coupling Reactions - Hempe, Matthias; Schnellbächer, Lutz; Wiesner, Tobias; Reggelin, Michael (Synthesis, 2017)
Herein, a synthetic approach using selective transition-metal-catalyzed cross-coupling reactions to thermally crosslinkable OLED materials based on vinyl-functionalized arylamines is reported. In a modular approach, 9,9-dialkyl-2,7-diiodo-9H-fluorene underwent a selective Ullmann cross-coupling reaction with bromo-substituted-diphenylamines to give 9,9-dialkyl-2,7-bis(bromo-substituted-diphenylamino)-9H-fluorenes that underwent end-functionalization by the Suzuki–Miyaura reaction using potassium vinyltrifluoroborate to give the corresponding 9,9-dialkyl-2,7-bis(vinyl-substituted-diphenylamino)-9H-fluorenes. Novel meta-functionalized materials were synthesized, which are difficult to prepare by traditional synthetic pathways. The thermal behavior of the compounds was investigated by DSC measurements, indicating a lower thermal sensitivity of the meta-substituted materials than their para-functionalized analogues.
Keywords: cross-link; vinylation; OLED materials; Suzuki–Miyaura; solution-processing; DSC